Piano sonata no. 5, op. 10, no. 1, edited by Winkler, with Winkler's metronome markings - Beethoven, Ludwig van, 1770-1827 (2025)
Piano sonata no. 5 in C minor, op. 10, no. 1, edited by Winkler, with Winkler's metronome markings